On the complexity of analyzing armed opposition: objectives, labeling, and reflections on Ethiopia’s Somali Region - Ylönen, A. (Journal of African History, Politics and Society, 2015)
Since the end of the Cold War, a significant number of armed conflicts have taken place in Africa. Most of these conflicts have occurred within states and many African governments have faced opposition movements resorting to violence and armed struggle. However, the political claims and trajectories of armed opposition groups have differed to a large degree in relation to their distinct political contexts. While some have become considerably apolitical over time, others have sought to live up to their initially-stated ideologies and objectives. Moreover, the often complex, disputed, and fragmented nature of the leaderships of armed opposition organizations in Africa tends to mask their ultimate political objectives, which are usually difficult to pinpoint. This article presents a selection of tentative findings from a study on armed opposition groups in the greater Horn of Africa. Focusing on the Ogaden National Liberation Front (ONLF) in Ethiopia, it highlights the problems associated with determining the political objectives of armed opposition organizations, as well as the difficulties associated with labeling such groups. The article argues that denominating rebel groups as “terrorist” serves to justify certain approaches towards them, while categorizing them as “secessionist” may not be analytically useful and may also indicate a possible political bias by creating a social boundary that can be used to justify particular policies towards the designated “other”.